Distribution of heavy metals in sediments and soft tissues of the Cerithidea obtusa from Sepang River, Malaysia - Krishnan, Kumar; Saion, Elias; Yap, Chee Kong; Balu, Prakash; Cheng, Wan Hee; Chong, Mee Yoke (Gadjah Mada University, 2022)
The main purpose of the research was to analyze the distribution of Arsenic (As), Cadmium (Cd), Copper (Cu), Iron (Fe), Nickel (Ni), Cobalt (Co), Mangan (Mn), and Zinc (Zn) in soft tissues, shells, and associated surface sediments of Cerithidea obtusa (C. obtusa) mangrove snails collected from Sungai Besar Sepang. The concentration of iron (Fe) was found to be the highest in relation to other toxic elements in sediments, soft tissues, and shells of C. obtusa. The concentrations of Cu and Zn in soft tissues of C. obtusa were found to exceed the concentrations in sediments, indicating bioaccumulation of these metals. Metal pollution was assessed with the Enrichment Factor (EF), Geoaccumulation Index (Igeo), and Pollution Factor (CF). EF, Igeo, and CF were 0.34 to 22.41, -3.37 to 2.65, and 0.14 to 9.42, respectively. The results indicate that sediments in Sungai Besar Sepang are contaminated with As and Zn. According to the bivalve bioaccumulation results, the soft tissues of C. obtusa act as a macro-concentrator for Cu and Zn. As a result, it is suggested that ongoing monitoring of releases of heavy metals from anthropogenic sources and stricter environmental protection measures should be implemented.